2006
DOI: 10.1111/j.1365-2036.2006.02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Oesophagitis is common in patients with achalasia after pneumatic dilatation

Abstract: SUMMARYBackground Achalasia, an oesophageal motor disease, is associated with functional oesophageal obstruction. Food stasis can predispose for oesophagitis. Treatment aims at lowering of the lower oesophageal sphincter pressure, enhancing the risk of gastro-oesophageal reflux. Nevertheless, the incidence of oesophagitis after achalasia treatment is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
0
23
1
Order By: Relevance
“…In achalasia patients, it has been suggested that chronic food stasis leads to chronic inflammation, epithelial hyperplasia, multifocal dysplasia, and squamous cell carcinoma (SCC) [1,16,17]. Previous studies showed that it would take a mean of 24 (range 10–43) years to establish carcinoma after symptom onset, and 3 to 4 years for carcinoma to develop from dysplasia [1,18,19]. Goldblum et al noted that several epithelial abnormalities were seen in achalasia, including high-grade squamous dysplasia, superficial squamous cell carcinoma, and lymphocytic esophagitis [20], exclusively accompanied by diffuse squamous hyperplasia reflecting accelerated cellular turnover and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In achalasia patients, it has been suggested that chronic food stasis leads to chronic inflammation, epithelial hyperplasia, multifocal dysplasia, and squamous cell carcinoma (SCC) [1,16,17]. Previous studies showed that it would take a mean of 24 (range 10–43) years to establish carcinoma after symptom onset, and 3 to 4 years for carcinoma to develop from dysplasia [1,18,19]. Goldblum et al noted that several epithelial abnormalities were seen in achalasia, including high-grade squamous dysplasia, superficial squamous cell carcinoma, and lymphocytic esophagitis [20], exclusively accompanied by diffuse squamous hyperplasia reflecting accelerated cellular turnover and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The most feared complication, esophageal perforation, occurred in 1.6% (range, 0.67-5.6%) of patients in a meta-analysis of 1,065 patients treated by experienced physicians [3,27]. After balloon dilation, the damaged LES allows gastric contents to more easily reflux into the esophagus, and up to 40% of patients develop chronic active or ulcerating esophagitis after dilatation [32,33,36], although only 4% are symptomatic [37].…”
Section: Dilatationmentioning
confidence: 97%
“…These factors usually lead to chronic inflammation of the esophageal mucosa, which potentially increases the risk of hyperplasia, dysplasia, and esophageal cancer [2, 3]. …”
Section: Introductionmentioning
confidence: 99%